One-pot synthesis of heterodimeric agonists that activate the canonical Wnt signaling pathway. Issue 25 (2nd March 2020) - Mukherjee, Abhirup; Stathos, Mark E.; Varner, Chad; Arsiwala, Ammar; Frey, Steven; Hu, Yuge; Smalley, David M.; Schaffer, David V.; Kane, Ravi S.
Abstract : Heterodimers synthesized by conjugating anti-Frizzled and anti-LRP6 Fabs using SpyTag–SpyCatcher chemistry activate the canonical Wnt signaling pathway. Abstract : Fragment antigen-binding domains (Fabs) from anti-Frizzled and anti-LRP6 monoclonal antibodies were conjugated using SpyTag–SpyCatcher chemistry via a one-pot reaction. The resulting synthetic heterodimeric agonist outperformed the natural ligand, Wnt-3a, in activating canonical Wnt signaling in mammalian cells. This approach should be broadly applicable to activate receptor-mediated cellular signaling.